Bond Fund Versus Islam Bond Fund: A Comparison of the Performance of Fixed Income Funds in Malaysia - Aminah Shari; Mohd Zulkarnain Bahrun (Human Resource Management Academic Research Society, 2023)
This study examines 43 bond funds and 24 Islamic bond funds in Malaysia from 1 August 2016 to 30 July 2021. This study analyses the performance of fixed income fund portfolios using risk-adjusted models: Treynor ratio, Sharpe ratio, and Jensen alpha. The Wilcoxon signed rank test was done on the top 20 bond funds and Islamic bond funds portfolios to compare risk adjusted performance using Sharpe, Treynor, and Jensen. Sharpe and Treynor's top 20 bond fund portfolios underperformed the market, while Islamic bond funds outperformed. Both funds outperform the market, according Jensen alpha. The performance of bond funds and Islamic bond funds differs significantly when three risk-adjusted models are utilised. This analysis reveals that Islamic bond funds are more stable over this time span.